BENTUK-BENTUK JAMINAN SOSIAL DAN MANFAATNYA BAGI TENAGA KERJA DALAM HUKUM KETENAGAKERJAAN INDONESIA - Junaidi Abdullah (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2018)
Labor in carrying out his work certainly has arisk of risk thatis likely to occur to the worker himself, both the risk o illnessresulting from his job, the risk of accident, the risk ofdisability, the risk of losing his jib and even the risk of death.Social security for the labor is a protection and will providebenetits for thr laboritself and for the family from unexpectedthing due to the risk possed in carrying out their work.Forms of social security for workers include : work accidentinsurance, old age insurance, pension insurance and lifeinsurance.